EKSPLORASI SENYAWA BIOAKTIF TERIPANG HITAM Holothuria atra ASAL PANTAI PANGANDARAN DAN POTENSINYA SEBAGAI ANTIJAMUR PRODUK PANGAN : Exploration Of Bioactive Compounds Of Black Sea Cucumber (Holothuria atra) and Its Potential as Antifungal Food Product - Nurhamzah, Lutfi Yulmiftiyanto (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2024)
Black sea cucumbers (Holothuria atra.) live in Indonesian waters, especially on the coast of Pangandaran district. Black sea cucumbers are believed to contain bioactive compounds that can have a positive impact on health. Bioactive compounds found in sea cucumbers in several regions in Indonesia have the potential to act as antifungals in food products. Information regarding the potential bioactive compounds of black sea cucumbers (H. atra) in Pangandaran district waters has not been reported. This research aims to determine the bioactive compounds of H. atra in Pangandaran district and their potential as anti-fungal food products. Fresh sea cucumber samples were prepared by removing the entrails, then cutting into 1x1 cm cubes. The black sea cucumbers are then macerated using three types of solvents separately. The three types of solvents used are ethanol, ethyl acetate and n-hexane in a ratio of 1:4. Black sea cucumbers are macerated for 3x24 hours. After that, the extract was evaporated using a rotary evaporator to obtain pure extract. The extract was then calculated for yield, analysis of water content, saponins, flavonoids, phenols, alkaloids and triterpenoids. Calculation of the yield results showed that ethanol was higher, namely 4.9%, while the extract yield using ethyl acetate solvent was 0.28% and the extract yield using n-hexane solvent was 0.75%. The bioactive compounds contained in sea cucumber extract using ethanol, ethyl acetate and n-hexan solvents include flavonoids, phenols and saponins. This shows that sea cucumber extract has the potential to be used as a natural antifungal for food products.